Influence of quality of work life and work-family interface on job satisfaction among employees in governmental organizations in Iran - Nekouei, Mohammad Hossein (2013)
The problem addressed in the study was the low rate of productivity that mainly originates from low level of job satisfaction. Studies in this respect have indicated that job dissatisfaction among employees in governmental organizations is one of the most common problems with many negative consequences. The objective of the study was to determine the influence of quality of work life,work family interface on job satisfaction among employees in governmental organizations in Iran, as well as factors that contribute toward their level of job satisfaction. The study was conducted among workers in government sector in Iran. Samples consisted of 485 respondents selected through stratified random sampling. Data collection was conducted in May 2010, based on self administered questionnaires.The questionnaire used consisted of a number of dimensions: a) personal characteristics; b) Job features, c) family characteristics; d) quality of work life, e) work family interface and f) job satisfaction. The structural equation modelling (SEM) was conducted to determine relationship between variables in the model (level of quality of work life, work family interface and job satisfaction). In order to being confident about the result and better estimate the relationship between the variables, both maximum likelihood and the Bayesian estimation was employed statistical analysis. The results of the study showed that: quality of work life and work family interface were significantly influence on job satisfaction; managerial dimensions of quality of work life and work family conflict make a better predictor for job satisfaction among employees in governmental organizations. Implications of this study will be particularly interesting to administrative system,managers of organizations, employees, family and also private sector. For future research, the replication of the study could be carried out to private sector, industry,manufacturing, hospital and educational centre. Meanwhile, the other dimensions of the quality of work life and aspects of work family interface, such as work family facilitation can be added to improve the model.